Being a midwife in West Africa: Between sensory experiences, moral standards, socio-technical violence and affective constraints. (May 2021) - Jaffré, Yannick; Lange, Isabelle L.
Abstract: Despite a long history of maternal health programs, the quality of obstetric care and access to facility services remain inadequate in West Africa. Although several qualitative studies have described human resource and facility constraints impacting pregnancy care and the violent or disrespectful care of women during labor, the reasons behind these behaviors have not been elucidated. In order to understand midwives' experiences with caregiving, in 2017–2018 we conducted interviews with 24 professional midwives in Benin and Burkina Faso and examined their perspectives on their profession, obstetric practices and personal lives. By including emotional, sensorial, linguistic and social elements, this paper shows important discordances between the proposals made by programs (such as rural postings and financial disbursement projects) and midwives' socio-emotional duties and economic roles. The study also shows that midwives' attitudes towards their patients are linked to their considering childbirth to be a moral act. Midwives' mistreatment of women in labor corresponds to constant shifts between technical obstetric skills and value judgements concerning expressions of pain, sexuality and desire. In addition, midwives justify their violent practices through the urgency of the situation, especially during crowning. The provision of care and the effective implementation of maternal programs cannot be improved without taking these justifications into account and without constructing dialogues enabling midwives to reflect on their social and emotional constraints, their relationship to the sexuality of childbirth, and the reasons for their practices. We advocate for more methodical research and for midwifery training to include in-depth case studies such as this one which start from the practical difficulties midwives face, making it possible to improve the midwifery profession as it is lived and not as it is imagined by fragmented, ungrounded programs. Highlights: Explores the biographical elements of midwives' professional narratives in Benin and Burkina Faso Links midwives' sensory worlds with the quality of delivery care they can provide Highlights the gaps between the organization of delivery services and midwives' socio-economic responsibilities Explains the causes of violence exercised by midwives against parturients during childbirth Proposes that programs should be adapted to midwives' contexts to improve the quality of obstetric care